IMPLEMENTASI VARIASI METODE PEMBELAJARAN AKIDAH AKHLAK KELAS V DI MI MIFTAHUL ULUM KOTA BATU - Divya Azza Assyifa; Mohammad Afifulloh; Lia Nur Atiqoh Bela Dina (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2020)
This study aims to describe the implementation of a variety of moral learning methods in the fifth grade at MI Miftahul Ulum. The problem faced is the application of a variety of methods of moral learning as an effort in creating learning activities that encourage learning motivation and the completion of student enthusiasm for learning. Study used a qualitative method, where the data obtained were collected through observation, interviews, and documentation. The results of this study indicate that the use of a variety of learning methods can increase students' understanding of the material delivered by the teacher and make the learning atmosphere fun and not boring. In the implementation of variations in learning methods there are three stages, the first stage is planning learning implementation and consider several factors that are the success of using a learning method. the second stage is the implementation of learning in accordance with the lesson plans that have been made. The third stage is the analysis of supporting and inhibiting factors in the implementation of learning activities.